PERBANDINGAN PENGHINDARAN PAJAK, PROFITABILITAS, SOLVABILITAS, DAN LIKUIDITAS PADA PERUSAHAAN SEKTOR CONSUMER NON-CYCLICALS SEBELUM DAN SELAMA PANDEMI COVID-19 - Lorens, Manuel; Sandra, Amelia (Jurnal Akuntansi, 2024)
Tax avoidance refers to measures of tax deduction received by the government. Financial ratios are utilized in analyzing and monitoring company performance through the company’s income statement and statement of financial position. This research has a purpose to discern whether tax avoidance, profitability, solvability, and liquidity were different before and during the COVID-19 pandemic. Using the judgment sampling, 37 consumer non-cyclicals sector companies listed in Indonesia Stock Exchange were obtained during the period 2018 to 2021. The sample in this research is considered normally distributed based on the Central Limit Theorem theory due to the number of samples exceeds 30. The Paired-Samples T-Test indicates that tax avoidance has a significance probability < 0.05, meanwhile profitability, solvability, and liquidity have a significance probability > 0.05. This research concluded that differences are present in tax avoidance between before and during the COVID-19 pandemic. In addition, differences are not present in profitability, solvability, and liquidity between before and during the COVID-19 pandemic